A Literary Study on Moschus - Kyu Jae Lee; Hyu Chul Yoon; Jin Seon Lee; Ki Rok Kwon (Korean Pharmacopuncture Institute, 2005)
Objective : Literary investigation of existing data was conducted to verify effects of Moschus and its herbal acupuncture, and determine quality management through component analysis. Results : Following results were obtained through literary investigation. 1. Deer musk (Moschus) is dried navel gland secretions of the adult male musk deer. 2. Moschus is known to be effective for treating various febrile diseases, to revive senses, heart and abdominal pain, complications from cerebral hemorrhage, angina, and others. 3. Single dosage of Moschus is between and should not exceed 1g. Normally taken as powder or pill and may be used externally. 4. Moschus also has protective effects for the liver cells, and experiments revealed possible efficacies for hyperlipidemia, brain damage, hypertension, and etc. 5. For herbal acupuncture usage, Fel Ursi, Bezoar Bovis, and Moschus are used as a mixture (BUM), and it's known to be effective for protecting the liver and treating arthritis. 6. For component analysis of Moschus, aromatic matter 'muscone' should be used as a standard matter.